Challenges and opportunities for agricultural development in West Africa - P. Kamara (Управление)
The article is about the challenges and opportunities for the development of the agricultural sector in West Africa. The aim of the study is to identify ways of improving the efficiency of agricultural production in West Africa, to increase yields. The task is to find, identify, develop and implement the most effective methods and algorithms for realising the above aim, and the challenges and obstacles along the way. The article describes the current state of agriculture in this sub-region. The author considers modern problems of agriculture in this territory, gives examples of agriculture in other regions of the world for comparison with West African. Intensive agriculture of various countries is considered as an option for the development of the West African region. The external factors, affecting the development of West African agriculture, in particular climatic change, increase in the average annual temperature, are considered. Attention is paid to the question of finding a new way of development of agriculture, resistant to climatic change. Possibilities and problems, related to the application of agroecology on the example of the Republic of Senegal, are analysed.